Perbandingan Proses Mineralisasi Karbon dan Nitrogen serta Humifikasi Pada Sistem Pertanian yang Berbeda di Tanah Andisol: Comparison of Carbon and Nitrogen Mineralization Processes and Humification in Different Agricultural Systems in Andisol Soil - Fajar Hidayanto; Retno Tri Purnamasari; Sari Widya Utami; Murni Handayani (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2025)
The organic farming system has become the choice of most farmers in Indonesia because it has a major impact on agricultural quality and soil fertility. Vegetable farming in Magelang and Semarang Regencies is cultivated on andisol soil which has a relatively high soil fertility level, but farmers still use organic fertilizers to increase the organic matter content of the soil. The organic farming system applies 10 tons ha-1 of cow manure, 20 liters ha-1 of liquid fertilizer, and the return of plant residues at each planting season. The conventional farming system with high organic matter applies 7 tons ha-1 of cow manure, 50 kg ha-1 of urea, 50 kg ha-1 of NPK fertilizer, 15 liters ha-1 of liquid fertilizer, while the conventional farming system with low organic matter applies 3 tons ha-1 of chicken manure, 50 kg ha-1 of ZA fertilizer, 50 kg ha-1 of KCl fertilizer, and 50 kg ha-1 of NPK fertilizer. Observation variables include pH NaF, C-organic, N-total, C/N ratio, humic acid, fulvic acid and humification rate. Data were analyzed for variety and if different, the method of the smallest significant difference test was continued. The results of the study showed that the organic farming system was more effective in increasing carbon and nitrogen in the soil and accelerating humification, so that nutrients were available more quickly. However, the deeper the soil layer, the mineralization and humification processes will decrease because they are greatly influenced by the availability of organic matter.